PENGARUH PROFITABILITAS, LIKUIDITAS, SIZE, KEPEMILIKAN INSTITUSIONAL, DAN TANGIBILITY TERHADAP STRUKTUR MODAL - Cahyani, Nilam Indah; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of profitability, liquidity, firm size, institutional ownership, andassets structure to the capital structure. The population is all manufacturing companies which are listed inIndonesia Stock Exchange in 2012-2015 periods. The sample collection technique has been carried out by usingpurposive sampling method and based on the predetermined criteria, 63 companies have been selected as samples.The data of the financial statement of the companies has been obtained from the official website of IDX andIndonesian Capital Market Directory (ICMD). This research has been carried out by using classic assumptiontest and multiple linear regressions analysis test which has been performed by using the SPSS statistics testversion 20.0. The result of the research shows that profitability and liquidity has negative influence to the capitalstructure. Institutional ownership and assets structure has positive influence to the capital structure.Meanwhile, firm size does not have any influence to the capital structure. The determination coefficient of theregression model which has been obtained is 0.807. It shows that the whole independent variables whichinfluence the dependent variable is 80.7% and the remaining 19.3% is influenced by other variables which arenot studied.Keywords: Performance Financial, Firm Size, Institutional Ownership, Assets Structure, Capital Structure.